Abortion in Asia local dilemmas, global politics - Whittaker, Andrea 1967- (Fertility, reproduction and sexuality, 2010)
The issue of abortion forces a confrontation with the effects of poverty and economic inequalities, local moral worlds, and the cultural and social perceptions of the female body, gender, and reproduction. Based on extensive original field research, this provocative collection presents case studies from 7 countries in Asia.